Migrating Literature: Reading Geling Yan’s The Banquet Bug and its Chinese Translations - Ying, Yan (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
Using Geling Yan’s The Banquet Bug and its Chinese translations as a case study, this article attempts to explore what I term “migrating literature” in a transnational and translational framework. Translation is reconceptualised at three levels: contextual, paratextual and textual. This article will first of all examine the very translational nature of immigrant writing from a contextualized reading. It will then look at how paratextual matters re-frame immigrant writing and sometimes impose meaning by analyzing two key paratextual elements, title and front cover. At the end, the gain and loss of meanings will be discussed at the textual level, with an emphasis on the ideological and cultural implications. It also points out the possibility of incorporating readings from translations in other languages and cultures, or translations in other media forms, into the framework of migrating literature.